2018
DOI: 10.31580/jmi.v15i1.72
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social media brand communication on Brand Knowledge: Mediating role of Brand Image & Brand Awareness Application of CBBE model theory of Keller

Abstract: In 21st century, where the use of social media is growing day by day. Individuals prefer social media for personal and professional use. Corporations are also communicating with their customers through the social media. Which increase awareness about the product of a specific brand. That ultimately develops brand knowledge. The basic objective of this study is to explore the relationship between the social media brand communication and brand knowledge by considering brand image and brand awareness as mediators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…These initiatives should be based on ethical principles, people's rights, and countries' needs (Hunt, 2019); and should promote the country's history as a main element to integrate all stakeholders' perspectives (Nas, 2017). When all of them agree on both historical and current elements, they can contribute to collectively building the country's brand (Bhatti et al, 2018). Our results showed that most media companies from France, Germany, Russia, and the United States did not refer to the UAE history when reporting about the Dubai Expo 2020.…”
Section: Discussionmentioning
confidence: 75%
“…These initiatives should be based on ethical principles, people's rights, and countries' needs (Hunt, 2019); and should promote the country's history as a main element to integrate all stakeholders' perspectives (Nas, 2017). When all of them agree on both historical and current elements, they can contribute to collectively building the country's brand (Bhatti et al, 2018). Our results showed that most media companies from France, Germany, Russia, and the United States did not refer to the UAE history when reporting about the Dubai Expo 2020.…”
Section: Discussionmentioning
confidence: 75%
“…Kita hidup di abad ke-21, di mana penggunaan media sosial berkembang dari hari ke hari dan orang-orang menggunakan media sosial untuk penggunaan pribadi dan professional (Bhatti, Arif, Mehar, & Younas, 2018). Penggunaan Twitter di Indonesia berpotensi sangat besar dan menunjukan jumlah yang signifikan, bahkan CEO Twitter sendiri mengatakan bahwa Indonesia sebenarnya memainkan peran sentral dalam perjalanan bisnis di Twitter (Susanto, 2017).…”
Section: Hasil Dan Pembahasan Isi Hasil Dan Pembahasanunclassified
“…The use of celebrities has been increasingly involved in marketing communication strategy because of their effectiveness in the communication process (Bhatti, Maraim&Arif,2017), and according to studies, celebrity use has an impact on consumer purchasing intentions reaches 88% (Smith,2011). New technologies have provided more opportunities for interaction between people and companies with each other (Bhatti, Mehar, Arif & Younas, 2017), and this development has been reflected in the relationship between marketers and brands, as accessing to the public is no longer linked only to companies, but by users who called the celebrities (Henning-Thurau et al, 2004). Therefore, companies put the consumers face to face with each other, and this makes purchasing decisions more easily (Muthiah & Kannan,2015), and gave them access to direct information from actual users of the brand (Kozinets,1999).…”
Section: 3impact Of Sales Promotion On Purchasing Behaviormentioning
confidence: 99%